Evolution of disease and potential Biocontrol activity of Trichoderma SP. against Rhizoctonia solani on potato - Matiar Rahman; M. Ayub Ali; Tapan Kumar Dey; M.M. Islam; Laila Naher; Ahmad Ismail (2014)
Black scurf and stem canker disease cause by the fungal pathogen of Rhizoctonia solani and it is